PEMANFAATAN PERPUSTAKAAN MADRASAH SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI MIN 10 HULU SUNGAI UTARA - Jamali Jamali (Sekolah Tinggi Agama Islam (STAI) Al-Wahliyah Barabai, 2023)
The existence of a madrasa library is not limited to a place to store textbooks, but must be able to present alternative sources of knowledge needed by students, because the existence of a library so far is still difficult for students to access. Moreover, there is a tendency for teaching patterns in Madrasahs to generally rely on package books determined by madrasa. Ironically, often the package book is from only one publisher and is selected based on the proximity of the government or madrasa managers to a particular publisher. This condition triggers the student's desire to search for reading sources or information outside the package book. The function of the madrasa library has received less attention, but the existence of the madrasa library depends on the commitment of school residents since teachers, students and the support of the head of the madrasa how to respond to it.